Selective Separation of Platinum in the Propyl-alcohol-Sodium Sulfate Two-phase Aqueous Extraction System - GAO†, YUNTAO; LIU*, XIAOHAI; TAO‡, YE; WANG§, JIAQIANG; WANG§, WEI; WU§, LISHANG; WANG, XIUEMEI (Asian Journal of Chemistry, 2009)
The extraction separation and phase distribution behaviours of iodide complexes of platinum(IV) in propyl-alcohol-sodium sulfate two-phase aqueous extraction system have been investigated. The amount of Na2SO4 added, the initial volume of propyl alcohol and the acidity of the system are mainly factors affecting the formation and phase separation of the aqueous two-phase system. Platinum(IV) is found to be extracted into the propyl alcohol phase due to ion pair formation of platinum(IV) as [Pt I62-·2(PrOH2+)2] in the presence of KI and HCl medium. The experimental results indicate that platinum can be quantitatively and highly selectively extracted by the optimized method, using which > 99.0 % extraction efficiency can be achieved. The proposed method has been successfully applied to the selective separation of platinum from samples containing large amount of base metals including Fe2+, Ca2+, Mg2+, Mn2+, Al3+, Pb2+ and Zn2+ in synthetic sample and exhibits high selectivity to platinum.